2016
DOI: 10.1038/ncb3400
|View full text |Cite
|
Sign up to set email alerts
|

A single dividing cell population with imbalanced fate drives oesophageal tumour growth

Abstract: Understanding the cellular mechanisms of tumour growth is key for designing rational anti-cancer treatment. Here we used genetic lineage tracing to quantify cell behaviour during neoplastic transformation in a model of oesophageal carcinogenesis. We found that cell behaviour was convergent across premalignant tumours, which contained a single proliferating cell population. The rate of cell division was not significantly different in the lesions and the surrounding epithelium. However, dividing tumour cells had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…Previous studies have demonstrated that clonal mutations to noncycling epithelial tissues, such as the skin epidermis or the esophageal epithelium, result in robust cellular competition that can ultimately influence the behavior and fate of their wild-type neighbors (Klein et al, 2010;Alcolea and Jones, 2015;Frede et al, 2016;Murai et al, 2018). To better understand how the Hras mutant cells are integrated into the tissue and whether their integration influences the fate of their wild-type neighbors, we performed revisit imaging of follicles over time.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that clonal mutations to noncycling epithelial tissues, such as the skin epidermis or the esophageal epithelium, result in robust cellular competition that can ultimately influence the behavior and fate of their wild-type neighbors (Klein et al, 2010;Alcolea and Jones, 2015;Frede et al, 2016;Murai et al, 2018). To better understand how the Hras mutant cells are integrated into the tissue and whether their integration influences the fate of their wild-type neighbors, we performed revisit imaging of follicles over time.…”
Section: Resultsmentioning
confidence: 99%
“…To track the fate of basal cells, Lrig1-cre mice were crossed with the Rosa26 flConfetti/wt (Confetti) reporter strain which labels cells with one of four possible fluorescent proteins (green, GFP, cyan, CFP, yellow, YFP or red RFP) after recombination ( Fig. S6C-D) 25,26 . In some Cre inducible mouse lines, reporter expressing clones can appear without induction with Tamoxifen.…”
Section: Clonal Dynamics In Esophageal Epitheliummentioning
confidence: 99%
“…Consequently, this mutation results in the exponential expansion of the stem cell pool. It resembles the behaviour of the dividing tumour cells with a strong bias toward generating dividing over non-dividing daughter cells through cell division [83].…”
Section: Discussionmentioning
confidence: 82%